Prevalence of Plasmid-Mediated Quinolone Resistance Determinants and OqxAB Efflux Pumps among Extended-Spectrum β-Lactamase Producing Klebsiella pneumoniae Isolated from Patients with Nosocomial Urinary Tract Infection in Tehran, Iran - Mehdi Goudarzi; Mehdi Azad; Sima Sadat Seyedjavadi (Scientifica)
Objective. Plasmid-mediated quinolone resistance (PMQR) plays an important role in the development of clinical resistance to quinolone. The aim of this study was to investigate PMQR determinants among extended-spectrum β-lactamases- (ESBL-) producing Klebsiella pneumoniae recovered from patients with nosocomial urinary tract infection (UTI). Methods. A total of 247 ESBL-producing K. pneumoniae isolates were collected from 750 patients with UTI. ESBL production was confirmed by double disc synergy test and combined disc diffusion test. The prevalence of PMQR determinants among ESBL-producing K. pneumoniae was assessed using PCR method. Results. The rates of resistance to antimicrobial agents in present study varied from 14.2% to 98.8%. In comparison with other PMQR genotypes, the frequency of aac(6′)-Ib (68.8%) was strikingly high. Of the 247 isolates tested, qnrA, qnrB, qnrS, and qepA genes were present in 3.6%, 1.6%, 1.2, and 2%, respectively. oqxA and oqxB were detected in 56.7% and 54.6% of isolates. The predominant coexisting ESBL and PMQR profile among our isolates included blaCTX-M and aac(6′)-Ib, oqxA, oqxB (28.3%) and blaTEM, blaSHV and aac(6′)-Ib, oqxA, and oqxB (19.4%) profile.  Conclusion. Given the linkage observed between resistance to quinolones and beta lactam antibiotics, therapeutic protocol with fluoroquinolones and beta lactam antibiotics should be seriously revised in Tehran hospitals.